2006
DOI: 10.1158/1535-7163.mct-06-0305
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 inhibition sensitizes neuroblastoma to chemotherapy-induced apoptotic cell death

Abstract: Novel therapeutic approaches are urgently needed for high-stage neuroblastoma, a major therapeutic challenge in pediatric oncology. The majority of neuroblastoma tumors are p53 wild type with intact downstream p53 signaling pathways. We hypothesize that stabilization of p53 would sensitize this aggressive tumor to genotoxic chemotherapy via inhibition of MDM2, the primary negative upstream regulator of p53. We used pharmacologic inhibition of the MDM2-p53 interaction with the small-molecule inhibitor Nutlin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 45 publications
7
113
1
2
Order By: Relevance
“…This favors a reduction of the dose of the chemotherapeutic agent to prevent the side effects without losing its effect as anti-cancer drug. Earlier studies have shown that Nutlin-3 is a potent sensitizer for standard radio-and chemotherapy (Barbieri et al, 2006;Cao et al, 2006;Coll-Mulet et al, 2006;Patton et al, 2006). Therefore, Nutlin-3 was combined with doxorubicin, which resulted in increased cell death, even with concentrations of doxorubicin that by itself had very little effect on cell survival.…”
Section: Regulation Of Drug Response By Mdm4mentioning
confidence: 99%
See 1 more Smart Citation
“…This favors a reduction of the dose of the chemotherapeutic agent to prevent the side effects without losing its effect as anti-cancer drug. Earlier studies have shown that Nutlin-3 is a potent sensitizer for standard radio-and chemotherapy (Barbieri et al, 2006;Cao et al, 2006;Coll-Mulet et al, 2006;Patton et al, 2006). Therefore, Nutlin-3 was combined with doxorubicin, which resulted in increased cell death, even with concentrations of doxorubicin that by itself had very little effect on cell survival.…”
Section: Regulation Of Drug Response By Mdm4mentioning
confidence: 99%
“…Owing to these characteristics, Nutlin-3 has been tested for its synergistic effects with existing therapies. It has been shown that treatment with Nutlin-3 is synergistic with genotoxic drugs and radiation in cancer therapy (Barbieri et al, 2006;Cao et al, 2006;CollMulet et al, 2006;Patton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While this work was ongoing, several new studies confirm the synergism of Nutlin in chemotherapeutic control of NB cells in culture. 38,39 In sum, our findings identify p53 hyperubiquitylation as a mechanism that contributes to cytoplasmic sequestration and attenuation of p53 function in NB. This p53 hyperubiquitylation is due to an impaired p53-HAUSP interaction but can be reversed by inhibiting the p53-Hdm2 interaction.…”
Section: Discussionmentioning
confidence: 66%
“…If the feedback loop is interrupted by an agent such as Nutlin-3a, the tumor cell will undergo apoptosis. Nutlin-3a has been studied as an effective agent to induce cell cycle arrest and apoptosis in some tumors, and has been found to increase radiosensitivity of H460 and Val138 cells [16], and to sensitize cells to chemotherapeutic agents such as cisplatin and etoposide [17]. To date, there has been no study of Nutlin-3a as a chemosensitizer for the commonly used agent paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Nutlins can release p53 from the negative control of MDM2 and activate the p53 pathway to promote cell cycle arrest and apop-tosis in cancer cells that express wild-type p53. Nutlin-3a increases radiosensitivity of H460 and Val138 cells [16], and sensitizes cancer cells to chemotherapeutic agents such as cisplatin, and etoposide [17]. However, some researchers found that Nutlins can protect non-malignant cells and tissues [18,19].…”
mentioning
confidence: 99%